To Study the Relationship between Job Satisfaction and Organisation Culture at Bikanervala - Sharma, Bhawna (Journal of Advanced Research in Humanities and Social Sciences, 2021)
With the help of the instrument example OCTAPACE, organization culture can be defined. OCTAPACE is all about and what are eight values that may be examined to develop the profile of an organizational culture. This study is limited to employee working in Bikanervala (Bikano). The present study is a descriptive study based on both primary and secondary data and Sample size 108 will include managerial employees and supervisor and workers. Simple random sampling technique will be adopted. Independent t test, correlation analysis (pearson) and regression analysis (simple regression) is applied to test the hypothesis to satisfy the stated objectives. Statistical package for social sciences (SPSS) and Microsoft excel (Ms Excel) is used as tools for data analysis. How to cite this article:  Sharma B. To Study the Relationship between Job Satisfaction and Organisation Culture at Bikanervala. J Adv Res Humani Social Sci 2020; 7(4): 20-25.